The differences between broad bean koji fermented in laboratory and factory conditions by an efficient Aspergillus oryzae - Li, Heng; Lu, Zhen-Ming; Deng, Wei-Qin; Zhang, Qi-Sheng; Chen, Gong; Li, Qi; Xu, Zheng-Hong; Ma, Yan-He (Frontiers in Microbiology, 2023)
Broad bean paste-meju was fermented by the mixture of broad bean koji and saline, koji fermentation is an essential process for the production of broad bean paste-meju. Aspergillus oryzae was the most widely used in sauce fermentation. The purpose of this study was to research the factory adaptability of the highly efficient A. oryzae PNM003, and further evaluate the effect of fermentation conditions and fermentation strains on koji. A. oryzae PNM003 was compared with the widely used strain HN 3.042 not only in the laboratory but also in factory conditions (large scale). Results showed the koji made with the same starter in the factory had a greater number of fungi amount than in the laboratory. Bacteria and yeast amounts of HN_L koji were more than PN_L koji. As for fungi constitution, there was almost only Aspergillus survived in the end through the microorganism self-purification during koji fermentation. As for bacteria constitution, koji was grouped by fermentation conditions instead of fermentation starter. PN koji had higher protease activity; higher content of total acids, amino acid nitrogen, amino acids, and organic acids in the laboratory conditions. Nevertheless, in the factory condition, PN koji and HN koji were similar in these indexes. As for volatile flavor compounds, koji made with the two starters in the same condition were grouped together. As for the same starter, there were more flavor compounds metabolized in the factory condition than in the laboratory condition especially esters and alcohols. The results showed PN was a highly efficient strain to ferment koji, but the advantages were expressed more remarkably in lab conditions. In a word, the fermented condition made greater influence than the fermentation starter for broad bean koji.